Mite diversity suborder Prostigmata associated with the plant rhizosphere soil of the Yotoco Nature Reserve, Valle del Cauca-Colombia (2017)
Yotoco Nature Reserve is a protected area for conservation purposes, is located at 3o53'18'' N, 76o20'5'' W, in the town of Yotoco with an altitude of 1526 m. a. s. l. The present research aimed to identify the diversity of mite suborder Prostigmata associated with the rhizosphere of plants of the Natural Reserve of Yotoco. Six samplings of soil and leaf litter between the surface and 5 cm depth were done in a radius of 1 m from the stem of plants, which are representative in each location of study. Samples were taken to the laboratory in styrofoam coolers. To isolate the mites, the Berlese-Tulgren funnel was used and mites were collected in vials with 70% alcohol. For permanent mounting in microscope slides, the Hoyer medium was used. A completely randomized block design with stratified replicates was used. The total of collected individuals was 181 and they were distributed in the following mite families: Microtrombidiidae, Stigmaeidae, Cunaxidae, Bdellidae, Pseudocheylidae, Cryptognathidae, Eupalopsellidae and Scutacaridae. The Stigmaeidae family was the most abundant and frequent. Among the identified mite families, 15 genera were found, from which, the genera Stigmaeus Koch, 1836 was the most common.